KINEMATIC-POSTURAL IMPLICATION OF TEXTURIZED INSOLES IN INDIVIDUALS WITH MULTIPLE SCLEROSIS: A SYSTEMATIC REVIEW - Cortés-Pérez , I; Obrero-Gaitán , E; Estévez-Martín , M J; García-Burcio , X (Cuestiones de Fisioterapia, 2020)
Objective: to analyze the balance and postural kinematic benefits that texturized insoles produce on the sti-mulation of the plantar mechanoreceptors and the somatosensory and proprioceptive afference in subjects with Multiple Sclerosis. Material and method: a systematic peer review was made. In the bibliographical search pro-cess, different health sciences databases were used (Pubmed Medline, Scopus, PEDro, Cuiden Plus, CINAHL y WOS). Randomised controlled trial and observational studies were required. There were no restrictions regar-ding language of publication, databases free access or full text availability. Results: finally, 4 studies met the in-clusion criteria and were included in this systematic review. An increase in stride length and an improvement in kinematics were observed, with an increase in extension and maximum knee flexion. The plantar sensation in-creased in patients with Multiple Sclerosis (p < 0.01). A reduction of the oscillation speed was required in the postural control parameter in the patients with sclerosis multiple who used the textured insoles. Conclusion: it is estimated that texturized templates improve gait parameters (step increase, stride and decrease in the speed of oscillation) and the perception of foot sensitivity in patients with Multiple Sclerosis. It should be added that these templates do not have an immediate effect and there is a doubt as to whether they were a placebo or learning effect and therefore further studies are proposed to clarify these effects.